SYNTHESIS OF THE BETULINIC ACID (Scientific journal of the Fergana State University, 2023)
Today, one of the most important tasks for the further development of the pharmaceutical industry is medicines obtained from local raw materials. This article describes the production of betulin from the bark of the Betula pendula tree growing on the territory of Uzbekistan, the synthesis of various derivatives based on it, and the study of the structure of substances by physical methods. Based on these studies, medicines will be created from local raw materials.